Knowledge of medical specialists on the emergency management of hyperkalaemia with a focus on insulin-based therapy - Chothia, Mogamat-Yazied; Chikte, Usuf; Davids, Mogamat Razeen (African Journal of Nephrology, 2022)
Introduction: Hyperkalaemia is a common electrolyte disorder in hospitalised patients and may cause life-threatening cardiac arrythmias and death. There is a lack of consensus regarding its optimal management, which may result in wide variations in practice and the guidance provided to junior staff. Methods: We conducted a survey on a Research Electronic Data Capture (REDCap) platform to evaluate the knowledge of medical specialists regarding the diagnosis and management of hyperkalaemia, with a focus on insulinbased therapy. A convenience sample of 70 specialists in nephrology, internal medicine, emergency medicine and critical-care medicine were invited to participate. Comparisons were also made between nephrologists and nonnephrologists. Results: A total of 51 medical specialists responded, of whom 47% were nephrologists. They were more likely to initiate therapy at a potassium concentration ([K]) of 6 mmol/L, whereas non-nephrologists tended to start at a lower concentration (P < 0.01). Half the respondents regarded blood gas machine measurements as providing an accurate measure of [K]. Non-nephrologists were more likely to perform an ECG before starting treatment (P = 0.02). All respondents regarded insulin and dextrose as the most effective and reliable means for shifting K. Only 22% monitored the serum glucose concentration beyond 2 hours following insulin-based therapy, and 22% thought that hypoglycaemia was an uncommon complication if dextrose also was administered. Conclusions: This is the first comprehensive survey to report on the knowledge of specialists regarding the emergency management of hyperkalaemia. There is a need to address knowledge gaps, particularly around the optimal and safe use of insulin-based therapies. Our findings and recommendations should be useful in informing the development of consensus guidelines and educational resources on hyperkalaemia.